2016
DOI: 10.1370/afm.1937
|View full text |Cite
|
Sign up to set email alerts
|

Using Best-Worst Scaling to Understand Patient Priorities: A Case Example of Papanicolaou Tests for Homeless Women

Abstract: PURPOSE Best-worst scaling (BWS) is a survey method for assessing individuals' priorities. It identifies the extremes-best and worst items, most and least important factors, biggest and smallest influences-among sets. In this article, we demonstrate an application of BWS in a primary care setting to illustrate its use in identifying patient priorities for services. METHODSWe conducted a BWS survey in 2014 in Boston, Massachusetts, to assess the relative importance of 10 previously identified attributes of Papa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 32 publications
0
35
0
1
Order By: Relevance
“…All analyses were conducted in Stata version 15 [44] and Microsoft Excel [45]. In other BWS studies, standardised scores have been shown to provide similar information to regression coe cients from a conditional logistic regression model, but with a greater ease of both interpretation and calculation [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were conducted in Stata version 15 [44] and Microsoft Excel [45]. In other BWS studies, standardised scores have been shown to provide similar information to regression coe cients from a conditional logistic regression model, but with a greater ease of both interpretation and calculation [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…All the recruited farmers were visited between September 2018 and April 2019. The study used the best-worst scaling (BWS) object case method to gather the perspectives of the farm owner about the effectiveness of MIs for endometritis prevention and control [21,59]. This approach has been used for livestock disease management in many countries [21,22,26].…”
Section: Survey Designmentioning
confidence: 99%
“…BWS is a technique in which participants are presented with a list of objects and asked to choose the one object that they consider the best (most preferred) and the one object that they consider the worst (least preferred). [22][23][24] This allows for comparison of relative values across objects, something that is not possible with traditional Likert scale surveys. [22][23][24] As part of this technique, a subset of all objects is presented at a given time in a choice task and the participant completes a series of choice tasks where the objects in each task are systematically varied.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…[22][23][24] This allows for comparison of relative values across objects, something that is not possible with traditional Likert scale surveys. [22][23][24] As part of this technique, a subset of all objects is presented at a given time in a choice task and the participant completes a series of choice tasks where the objects in each task are systematically varied. *At the beginning of the choice tasks, additional description was given that stated: "Sometimes, if the doctor does not think a person needs a screening colonoscopy, the doctor may not mention colon cancer screening at all" †At the beginning of the choice tasks, additional description was given that stated: "The doctor may tell a person that he does not need a colonoscopy without giving a reason"…”
Section: Survey Instrumentmentioning
confidence: 99%